Incomplete Excision of Cutaneous Squamous Cell Carcinoma; Systematic Review of the Literature - Roel E. Genders; Nick Marsidi; Marlies Michi; Erik P. Henny; Jelle J. Goeman; Marloes S. van Kester (Medical Journals Sweden, 2020)
The treatment of choice for cutaneous squamous cell carcinoma is complete surgical excision. Incomplete excision of cutaneous squamous cell carcinoma has an increased risk of local recurrence, deep subclinical progression, and metastasis. This study aimed to investigate the proportion and risk factors of incomplete excised cutaneous squamous cell carcinoma. A systematic review of the literature was performed. Incomplete excision rates for cutaneous squamous cell carcinoma ranged from 0.4% to 35.7%. The pooled incomplete excision risk estimate was 13% (95% confidence interval 9-17%). Risk factors noted in more than one study for incomplete excision included tumor depth and size, type of operator, head and neck localization, and former incomplete excision. We found an overall incomplete excision rate of 13% for cutaneous squamous cell carcinoma. Risk factors should be taken into account in the management of cutaneous squamous cell carcinoma surgical treatment.